Retratos da migração transnacional na cidade de São Paulo : um estudo sobre o consumo imagético da exposição fotográfica "Somos Todos Imigrantes" - Passaro, Matheus Alves (2017)
This research analyzes the relations between communication, consumption and migrations from the study of the production and reception processes of the photographic exhibition "Somos Todos Imigrantes", seeking to understand the frameworks and perceptions surrounding the media visibility and of transnational immigrants in the city of São Paulo. The theoretical framework covers the conceptual field of communication, consumption, citizenship, image, visualities and migrations transnational corporations. The methodology of the research is based on bibliographic research and documentary; observation of production spaces and reception of the photographic exhibition; collection and exposure image analysis; interviews with producers and the immigrant public and not immigrant. The results of the research point to three main dimensions that resulting from the processes of production of the appropriations of the photographic exposure: (1) the recognition of a dominant media visibility that hierarchizes the immigrants and associates them with problem, conflict, poverty; (2) the possibilities of setting up other citizen visions, especially those that uniquely distinguish, without folklore, and favor a humanizing approach with the immigrant Other; and (3) the limits imposed other visibilities in the field of migration that the need for public policies that assure immigrants access to and occupation of both from the media and from the city .